POLYMER COMPOSITES FOR THERMAL AND CORROSION PROTECTION OF THIN-WALLED OPEN-PROFILE METAL STRUCTURES - Ibragimov, Baxrom; Norqulov, Fayzulla; Murtazayev, Eshmurod (Innovatsion texnologiyalar, 2024)
This article discusses the problems of assessing the technical condition of metal structures used at industrial production facilities, ensuring safety and reducing risks in construction. Development of technology for the emergence and protection of metal structures from corrosion in thin-walled steels. It is planned to increase the corrosion resistance of metal structures.